2018
DOI: 10.1111/xen.12443
|View full text |Cite
|
Sign up to set email alerts
|

A model for determining an effective in vivo dose of transplanted islets based on in vitro insulin secretion

Abstract: Increasing dosages of islet macrobeads transplanted into diabetic rats, based on multiples of in vitro insulin secretion matched to the recipient's exogenous insulin requirements, correlated with improved blood glucose regulation and increased duration of graft function. These results demonstrate the usefulness of a standardized model for the evaluation of the functional effectiveness of islets intended for transplantation, in this case using intraperitoneally implanted agarose macrobeads, in diabetic rats. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…56 Our islet dosing strategy was not based on IEQ per kg body weight, but instead was based on total 24 h insulin secretion per macrobead during in vitro culture. 57 Based on the non-optimal environment of the peritoneal cavity (e.g., oxygen and other nutritional limitations, inflammatory mediators) as compared to an incubator with precisely controlled parameters, we used a 2× dose of the estimated number of required macrobeads in an attempt to reduce the administration of exogenous insulin by half. Using this strategy, most animals in our study were able to decrease exogenous insulin by 30% or more during the first year of the study, suggesting that our dosing strategy still underestimated the required macrobead number to reliably achieve a 50% insulin reduction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…56 Our islet dosing strategy was not based on IEQ per kg body weight, but instead was based on total 24 h insulin secretion per macrobead during in vitro culture. 57 Based on the non-optimal environment of the peritoneal cavity (e.g., oxygen and other nutritional limitations, inflammatory mediators) as compared to an incubator with precisely controlled parameters, we used a 2× dose of the estimated number of required macrobeads in an attempt to reduce the administration of exogenous insulin by half. Using this strategy, most animals in our study were able to decrease exogenous insulin by 30% or more during the first year of the study, suggesting that our dosing strategy still underestimated the required macrobead number to reliably achieve a 50% insulin reduction.…”
Section: Discussionmentioning
confidence: 99%
“…The culture medium was changed weekly and 24‐h post‐change medium samples were taken for porcine‐insulin ELISA assays (Mercodia, Uppsala, Sweden) to measure average daily insulin secretion per macrobead for each production lot prior to implantation in diabetic animals (Table 1). This in vitro methodology provides a continuous timeline of 24‐h insulin production in response to high glucose media and has proven to be a reliable indicator of in vivo function 57,58 . Graphs of islet macrobead insulin production for each lot of macrobeads used in the current study are included as Figure S1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors found that adult porcine islets, which were defined as over two years old, had the strongest membranes and 50 times more insulin than younger cells . Holdcraft et al were interested in finding an appropriate dosage of islets to include in each encapsulation. They performed islet transplants of varying doses in rats, continuously testing blood sugar levels in vivo and later the insulin secretion in culture .…”
Section: Encapsulated Porcine Isletsmentioning
confidence: 99%
“…Holdcraft et al were interested in finding an appropriate dosage of islets to include in each encapsulation. They performed islet transplants of varying doses in rats, continuously testing blood sugar levels in vivo and later the insulin secretion in culture . The data suggest that multiple doses were better than a single dose in maintaining good blood sugar control …”
Section: Encapsulated Porcine Isletsmentioning
confidence: 99%